A new analytical method for calculating seismic displacements in reinforced retaining walls. Issue 3 (June 2012) - Mojallal, M.; Ghanbari, A.; Askari, F.
Abstract : ABSTRACT: Calculating the seismic displacement of reinforced retaining walls is important for optimal design of these structures. Using the limit analysis theorem, in this study an innovative approach has been proposed for calculating the coefficient of yield acceleration and permanent displacements of geosynthetic-reinforced soil-retaining walls with full-height rigid concrete facing (GRS-FHR walls). In this manner, based on the upper-bound theory of limit analysis and Newmark's sliding block theory, a group of charts has been proposed to estimate the permanent sliding displacements and the coefficient of yield acceleration for this type of wall. In these charts, the effect of the following parameters on the magnitude of permanent displacements and on the coefficient of yield acceleration of the wall has been investigated: vertical spacing of reinforcements; ratio of width to height of facing; ratio of length of reinforcements to height of facing; and internal friction angle of the soil. Results obtained from the suggested method have been compared with the sliding displacements reported by other researchers as well as those measured at the toe of a well-known GRS-FHR wall called Tanata under the Kobe earthquake (Japan, 1995). The suggested charts are believed to provide an appropriate, handy tool for estimating the coefficient of yield acceleration and permanent sliding displacements of GRS-FHR retaining walls.